“I am gay, and the LGBTQI+ movement does not represent me”: Mapping the emergence of right-wing gay activism in Brazil - Rodrigo Cruz (Cahiers des Amériques Latines)
The article seeks to map the emergence of right-wing gay activism in Brazil in recent years, particularly since 2013, when online activism initiatives based on a proudly right-wing gay identity started to multiply on social media. Initially it seeks to analyze the variables of the political environment that favored this type of engagement. Then the emergence of this collective actor is reconstituted in two arenas (online social media and the press) using data triangulation (virtual ethnography, documentary press research and interviews with activists). Finally the different styles of activism that seem to emerge from this process are analyzed, as well as some of the challenges that the phenomenon represents for the future of the struggle for LGBTQI+ rights in Brazil.